Provenance analyses of early Mesozoic sediments in the Ningwu basin: Implications for the tectonic–palaeogeographic evolution of the northcentral North China Craton. Issue 1 (2nd January 2019) - Zhou, Rui; Liu, Dongna; Zhou, Anchao; Zou, Yu
ABSTRACT: This paper reports results from detrital zircon U–Pb geochronology, Hf isotopic geochemistry, sandstone modal analysis, and palaeocurrent analysis of the early Mesozoic strata within the Ningwu basin, China, with the aims of constraining the depositional ages and sedimentary provenances and shedding new light on the Mesozoic tectonic evolution of the northcentral North China Craton (NCC). The zircons from early Mesozoic sandstones are characterized by three major populations: Phanerozoic (late Palaeozoic and early Mesozoic), late Palaeoproterozoic (with a peak at approximately 1.8 Ga), and Neoarchaean (with a peak at approximately 2.5 Ga). Notably, three Phanerozoic zircons in the Early Triassic Liujiagou Formation were found to have positive ε Hf ( t ) values and characteristics typical of zircons from the Central Asian Orogenic Belt (CAOB). Therefore, the CAOB began to represent the provenance of sediment in the sedimentary basins in the northern NCC no later than the Early Triassic (261 Ma), implying that the final amalgamation of the NCC and CAOB occurred before the Early Triassic. The U–Pb geochronologic and Hf isotopic results show that the Lower Middle Triassic sediments were mainly sourced from the Yinshan–Yanshan Orogenic Belt (YYOB), and that a sudden change in provenances occurred, shifting from a mixed YYOB and CAOB source in the Middle Jurassic to a primarily YYOB source in the Late Jurassic. The results of the sandstone modal analysis suggest that the majority of the samples from the Lower Middle Jurassic rocks were derived from either Continental Block or Recycled Orogen sources, whereas all the samples from the Upper Jurassic rocks were derived from Mixed sources. The change in source might be ascribed to the southward subduction and closure of the Okhotsk Ocean and the resulting intense uplift of the YYOB during the Late Jurassic. This uplift likely represents the start of the Yanshan Orogeny.